True Short Esophagus in Gastroesophageal Reflux Disease: Old Controversies With New Perspectives. Issue 2 (3rd August 2021) - Lugaresi, Marialuisa; Mattioli, Benedetta; Daddi, Niccolò; Bassi, Francesco; Pilotti, Vladimiro; Ferruzzi, Luca; Mattioli, Sandro
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To explore the true short esophagus (TSE) frequency and long-term results of patients undergoing gastroesophageal reflux disease (GERD) or hiatus hernia (HH) surgery. Background: The existence and treatment of TSE during GERD/HH surgery is controversial. Satisfactory long-term results have been achieved with and without surgical techniques dedicated to TSE. Methods: In 311 consecutive patients undergoing minimally invasive surgery for GERD/HH, the distance between the endoscopically-localized gastroesophageal junction (GEJ) and the apex of the diaphragmatic hiatus after maximal thoracic esophagus mobilization was measured. A standard Nissen fundoplication (SN) was performed in cases with an abdominal length >1.5 cm; in cases of TSE (abdominal length <1.5 cm), a Collis-Nissen (CN) or stomach around the stomach fundoplication (SASF) in elderly patients was performed. The fundoplication superior margin was fixed below the hiatus, but over the GEJ. The patients' symptoms, and radiological and endoscopic data were pre/postoperatively recorded. Results: After intrathoracic esophageal mobilization (median 9 cm), TSE was diagnosed in 31.8% of 311 cases. With a median follow-up of 96 months (309 patients), HH relapse was radiologically diagnosed in 3.2% of patients, with excellent, good, fair, and poor outcomes in 45.6%, 44.3%, 6.2%, and 3.9% of cases, respectively, and no significant differences among SN (68.5%), CN (26.4%), and SASF (5.2%). Conclusions: TSE was present in 31.8% of patients routinely submitted to GERD/HH surgery. In the presence of TSE, CN and SASF performed according to determined surgical principles may achieve similar satisfactory results. This finding warrants confirmation with a prospective multicenter study.